Victims versus veterans: agency, resistance and legacies of Timor-Leste’s truth commission - Rothschild, Amy (International journal of transitional justice, 2017)
This article examines the politics of victims’ rights in Timor-Leste a decade after Timor’s official independence from Indonesia. Using data from work and ethnographic fieldwork in Timor from 2002 to 2013, the article asks why Timor’s victims’ rights movement has had such difficulties achieving its goals, and whether and in what ways Timor’s truth commission has contributed to these difficulties. It argues that Timor’s victims’ rights movement has floundered because of the emergence of a gendered victim-veteran binary in Timor, in which the ‘victim’ is defined in negative relation to the ‘veteran’ as one who did not resist Indonesian rule and is devalued accordingly. It further argues that Timor’s truth commission unintentionally contributed to this binary through its discourse of innocent, suffering victimhood. The article concludes by examining how truth commissions can engage with the theme of past resistance to violence, so as to prevent the emergence of similar victim-veteran binaries elsewhere.